2016
DOI: 10.1016/j.rmed.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prevalence in German Olympic athletes: A comparison of winter and summer sport disciplines

Abstract: The clinically relevant finding of this study is that athletes' asthma seems to be more common in sports with high ventilation during competition, whereas the summer or winter season had no impact on the frequency of the disease. Among winter athletes, elevated FENO suggested suboptimal control of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
1
18
3
Order By: Relevance
“…It should be recognized that, according to the proposed mechanisms of development of asthma in athletes, winter and summer athletes may be exposed to different amounts of airway stress due to different exposure to environmental irritants, airborne allergens, and cold air. In fact, skiers were at a higher risk of incident physician-diagnosed asthma in our study; however, previous studies show somewhat conflicting results regarding the importance of season of competition (27,31).…”
Section: Discussioncontrasting
confidence: 66%
“…It should be recognized that, according to the proposed mechanisms of development of asthma in athletes, winter and summer athletes may be exposed to different amounts of airway stress due to different exposure to environmental irritants, airborne allergens, and cold air. In fact, skiers were at a higher risk of incident physician-diagnosed asthma in our study; however, previous studies show somewhat conflicting results regarding the importance of season of competition (27,31).…”
Section: Discussioncontrasting
confidence: 66%
“…It has been shown that German elite athletes with high ventilation rates use significantly more asthma medication than those with medium or low ventilation rates, but no significant difference in use was observed between summer and winter athletes [ 5 ]. These observations support our present findings regarding asthma medication and suggest that they may also be applicable to summer endurance athletes, such as long-distance runners and racing cyclists.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of asthma in Sweden is estimated to be 10% in the population aged 16–35 years [ 1 ]. However, the prevalence of asthma is higher in athletes, especially those participating in sports associated with high ventilation rates [ 2 5 ]. Recently, the prevalence of physician-diagnosed asthma among Swedish elite cross-country skiers was estimated at 35% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of asthma and asthma‐related conditions, such as exercise‐induced bronchoconstriction, inhaled beta 2 ‐adrenoceptor agonists (beta 2 ‐agonists) are among the most commonly used substances in competitive sports . As for many other substances, the World Anti‐Doping Agency (WADA) has imposed restrictions towards the use of all selective and non‐selective beta 2 ‐agonists both in‐ and out‐ of competition, being listed in the S3‐category (beta 2 ‐agonist specific category) on the 2020 Prohibited List .…”
Section: Introductionmentioning
confidence: 99%